2015
DOI: 10.1161/circresaha.116.305085
|View full text |Cite
|
Sign up to set email alerts
|

GPIHBP1 Missense Mutations Often Cause Multimerization of GPIHBP1 and Thereby Prevent Lipoprotein Lipase Binding

Abstract: Rationale GPIHBP1, a GPI-anchored protein of capillary endothelial cells, binds lipoprotein lipase (LPL) in the subendothelial spaces and shuttles it to the capillary lumen. GPIHBP1 missense mutations that interfere with LPL binding cause familial chylomicronemia. Objective We sought to understand mechanisms by which GPIHBP1 mutations prevent LPL binding and lead to chylomicronemia. Methods and Results We expressed mutant forms of GPIHBP1 in Chinese hamster ovary cells, rat and human endothelial cells, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(95 citation statements)
references
References 32 publications
3
92
0
Order By: Relevance
“…The amounts of LPL that moved to beads coated with GPIHBP1(25-50) and GPIHBP1-W109S (normalized to the amount of GPIHBP1 on the beads) averaged 87.9% and 23.3%, respectively, in three separate experiments. so without causing inappropriate intermolecular disulfide bond formation and protein multimerization (27). The discovery that GPIHBP1 lacking the acidic domain is capable of capturing LPL from HSPGs is consistent with recent findings by Mysling et al (24).…”
Section: Testing the Mobility Of Hspg-bound Lpl In Gpihbp1supporting
confidence: 89%
See 3 more Smart Citations
“…The amounts of LPL that moved to beads coated with GPIHBP1(25-50) and GPIHBP1-W109S (normalized to the amount of GPIHBP1 on the beads) averaged 87.9% and 23.3%, respectively, in three separate experiments. so without causing inappropriate intermolecular disulfide bond formation and protein multimerization (27). The discovery that GPIHBP1 lacking the acidic domain is capable of capturing LPL from HSPGs is consistent with recent findings by Mysling et al (24).…”
Section: Testing the Mobility Of Hspg-bound Lpl In Gpihbp1supporting
confidence: 89%
“…We produced secreted versions of human wild-type GPIHBP1, GPIHBP1-W109S, and GPIHBP1 in Drosophila S2 cells (27). These GPIHBP1 proteins contained a uPAR tag (27) and the epitope for the GPIHBP1-specific monoclonal antibody 11A12 (28).…”
Section: Preparation Of Soluble Human Gpihbp1mentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of missense mutations in GPIHBP1's LU domain have been identified in patients with chylomicronemia (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), and all of those abolish the ability of GPIHBP1 to bind LPL (6). Most of these mutations interfere with the formation of disulfide bonds in the LU domain, leading to disulfide-linked dimers and multimers (23). Alanine-scanning mutagenesis studies showed that the highly conserved second finger of the threefingered LU domain is particularly important for binding LPL (24).…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%